2014
DOI: 10.1073/pnas.1322269111
|View full text |Cite
|
Sign up to set email alerts
|

The microbial metabolite butyrate regulates intestinal macrophage function via histone deacetylase inhibition

Abstract: Significance The mammalian intestines contain an enormous number of microorganisms within the lumen. Given the constant exposure to these microbes, the intestinal immune system has the difficult task of maintaining tolerance to commensal bacteria while remaining responsive to potential pathogens. The mechanisms by which this balance is achieved are relatively unknown. Here, we identify a bacterial metabolite, n-butyrate, that exerts immunomodulatory effects on intestinal macrophages and renders them … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

44
1,233
1
11

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 1,585 publications
(1,289 citation statements)
references
References 44 publications
(45 reference statements)
44
1,233
1
11
Order By: Relevance
“…We previously observed that both germ-free and GPR43-deficient mice showed exacerbated immune responses and nonresolving inflammation in chronic diseases, such as colitis, arthritis, and asthma (12). Moreover, treatment with short-chain fatty acids ameliorated these conditions in conventional mice (43)(44)(45). Here, we show that short-chain fatty acids are necessary for acute inflammasome-dependent inflammatory responses.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…We previously observed that both germ-free and GPR43-deficient mice showed exacerbated immune responses and nonresolving inflammation in chronic diseases, such as colitis, arthritis, and asthma (12). Moreover, treatment with short-chain fatty acids ameliorated these conditions in conventional mice (43)(44)(45). Here, we show that short-chain fatty acids are necessary for acute inflammasome-dependent inflammatory responses.…”
Section: Discussionsupporting
confidence: 49%
“…Further studies are clearly needed to understand these issues in greater detail. Recent studies have shown that short-chain fatty acids negatively modulate chronic diseases in conventional mice (43)(44)(45). We previously observed that both germ-free and GPR43-deficient mice showed exacerbated immune responses and nonresolving inflammation in chronic diseases, such as colitis, arthritis, and asthma (12).…”
Section: Discussionmentioning
confidence: 99%
“…T cells in the colon express high levels of GPR43 receptor in response to microbiota and receptor engagement contributes to homeostasis of colonic regulatory T cells and their enhanced suppressive activity for prevention of colitis development [84]. Butyrate also modulates the immune response of macrophages in the gut lamina propria and reduces the production of proinflammatory mediators, IL-6, IL-12 and nitric oxide (NO) [85]. The CX3CR1 hi CD103 -intestinal macrophages are hyporesponsive to the gut microbiota [85].…”
Section: Inflammatory Bowel Disease (Ibd)mentioning
confidence: 99%
“…Butyrate also modulates the immune response of macrophages in the gut lamina propria and reduces the production of proinflammatory mediators, IL-6, IL-12 and nitric oxide (NO) [85]. The CX3CR1 hi CD103 -intestinal macrophages are hyporesponsive to the gut microbiota [85]. In comparison to regulatory T cells, the anti-inflammatory effect of butyrate on lamina propria macrophages is not mediated by GPR43 receptor but it acts as a histone deacetylase (HDAC) inhibitor [85].…”
Section: Inflammatory Bowel Disease (Ibd)mentioning
confidence: 99%
See 1 more Smart Citation